Transitional Justice in Tunisia Innovations, Continuities, Challenges - Robins, Simon; Gready, Paul (Transitional Justice, 2023)
This book engages comprehensively with the dynamics of the transitional justice process in Tunisia and its mechanisms, elaborating lessons for transitional justice practice globally. Grounded in new empirical material as well as a broader awareness of transitional justice, this book provides a comprehensive assessment of transitional justice in Tunisia. Beyond an overview of the process, it critically engages with key questions such as the extent to which the process articulated global contemporary practice, such as liberal state-building, and narrow conceptions of justice as civil-political rights, and to which it generated novel approaches, at odds with the mainstream, that can inform global practice. The book examines the extent to which the transitional justice process in Tunisia has been contextualised and made relevant to the nation's circumstances and needs. It looks at innovation at the level of formal mechanisms and at the dynamics of mobilization and contestation surrounding the transitional justice process, both from civil society organizations and victims' groups. Bringing together analysis from legal scholars, social scientists as well as activists and practitioners, the book challenges the legalism of transitional justice discourse globally, engendering a dialogue between these legal and judicial approaches on the one hand, and alternative, more diverse and radical approaches to justice on the other, in order to both deal with the past and to address ongoing injustice. This first book in English to address the dynamics and mechanisms of the transitional justice process in Tunisia will appeal to students and scholars of transitional justice, human rights, peacebuilding, conflict and peace studies, development, and security studies, as well as policy makers and practitioners in these fields, and others with interests in Middle Eastern studies.